Faktor-Faktor yang Mempengaruhi Penggunaan Informasi Akuntansi pada Usaha Mikro Kecil dan Menengah di Kabupaten Banyuwangi - Nindi Nadia Yurisma; Arik Susbiyani; Gardina Aulin Nuha (LPPM POLITEKNIK LP3I BANDUNG, 2023)
This study aims to analyze and determine the effect of business scale, education level and accounting knowledge on the use of accounting information in Micro, Small and Medium Enterprises in Banyuwangi Regency. The variables used in this study consisted of 3 independent variables, namely business scale (X1), education level (X2) and accounting knowledge (X3) and the variable used was the use of accounting information (Y). This study uses quantitative methods. Data collection is done by distributing it directly to MSME owners. The population in this study are micro, small and medium enterprises in Banyuwangi Regency with a total of 5,022. The research sample used was in accordance with the Slovin formula calculation of 98.4 (rounded 98) or the respondents used were 98. The sampling technique in this study used Simple Random Sampling. Analysis of the research data using multiple linear regression which is processed using IBM SPSS Statistics to determine the factors that influence the use of accounting information. The results of this study indicate that the variables of business scale, education level and accounting knowledge have a positive effect on the use of accounting information on MSMEs in Banyuwangi Regency.